Effect of Compensation, Training, and Work Motivation on Employee Performance in Coffee Shop - Mirza, Hanna Julia; Efendi, Nur; Saptiani, Fenny (Journal of Business Management and Economic Development, 2025)
The phenomenon of the development of a more modern coffee culture has made coffee shops emerge in various regions, one of which is in Enggal District, Bandar Lampung, and the need for coffee shop employees is increasing. Coffee shop employees have a very important role in running operations in coffee shops so that compensation, training and work motivation are factors that can affect the performance of coffee shop employees. This study aims to determine the effect of compensation, training, and work motivation on the performance of coffee shop employees in Enggal District, Bandar Lampung. This study uses a quantitative approach with an explanatory research type. The sample in this study was 340 coffee shop employees in Enggal District, Bandar Lampung, which was carried out using a non-probability sampling technique with a saturated sampling technique. Data collection was carried out through a digital questionnaire (Google Forms) and measurements using a likert scale. Data analysis was carried out using SPSS 30 statistical software. The results of the study showed that partially compensation, training, and work motivation had a positive and significant effect on employee performance. Simultaneously, these three variables had a significant effect on the performance of coffee shop employees in Enggal District, Bandar Lampung. These findings provide insight for coffee shops in providing compensation, training and work motivation to be more in line with the contributions made by employees, so that employee performance improves.